Ekstrakurikuler Olimpiade Sains sebagai Upaya Meningkatkan Prestasi Siswa Madrasah Ibtidaiyah pada Kompetisi Sains Madrasah Tingkat Nasional - Nino Indrianto; Maria Ulfah Shamilah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2020)
Being achievers in prestigious competition such as National Madrasah Science Competition (Kompetisi Sains Madrasah/KSM) is a dream of every student. One effort to improve students' achievements is by implementing extracurricular on science olympiad activities. This study aims to describe how science olympiad extracurricular as an effort to improve students' achievements of Madrasah Ibtidaiyah (MI) At-Taqwa Bondowoso in KSM. This study uses a qualitative approach with a case study. Data obtained through interviews, observations and documentation that were further analyzed using interactive models of Miles, Huberman and Saldana. The results of this study indicate that science olympiad extracurricular at MI At-Taqwa are designed with a goal to achieve an achievements in KSM. The implementation of the extracurricular is conducted intensively using variety methods by integrating theory and exercise. Besides, learning evaluation is based on higher order thinking skills (HOTS). Also, the results become a role model for other madrasah to improve students’ achievements in KSM. Therefore, madrasah can be as great and dignified as its motto.